Ethyl 4,4′′-difluoro-5′-methoxy-1,1′:3′,1′′-terphenyl-4′-carboxylate - Hoong-Kun Fun; Tze Shyang Chia; S. Samshuddin; B. Narayana; B. K. Sarojini (Acta Crystallographica Section E, 2012)
In the title compound, C22H18F2O3, the two fluoro-substituted rings form dihedral angles of 25.89 (15) and 55.00 (12)° with the central benzene ring. The ethoxy group in the molecule is disordered over two positions with a site-occupancy ratio of 0.662 (7):0.338 (7). In the crystal, molecules are linked by C—H...O hydrogen bonds into chains along the a axis. The crystal packing is further stabilized by C—H...π and π—π interactions, with centroid–centroid distances of 3.8605 (15) Å.